Reducing Both Pgp Overexpression and Drug Efflux with Anti-Cancer Gold-Paclitaxel Nanoconjugates - Li, Fei; Zhou, Xiaofei; Zhou, Hongyu; Jia, Jianbo; Li, Liwen; Zhai, Shumei; Yan, Bing (PLOS ONE, 2016)
Repeated administrations of anti-cancer drugs to patients often induce drug resistance. P-glycoprotein (Pgp) facilitates an efficient drug efflux, preventing cellular accumulation of drugs and causing multi-drug resistance (MDR). In this study, we developed a gold-paclitaxel nanoconjugate system to overcome MDR. Gold nanoparticles (GNPs) were conjugated with β-cyclodextrin enclosing paclitaxel (PTX) molecules and PEG molecules. GNP conjugates were effectively endocytosed by both drug-sensitive human lung cancer H460 cells and Pgp-overexpressed drug-resistant H460PTX cells. Compared with PTX, PGNPs did not induce the Pgp overexpression in drug-sensitive H460 cells after long-term treatment and also avoided being pumped out of cells by overexpressed Pgp molecules in H460PTX with a 17-fold lower EC50 compared to PTX. Fluorescent microscopy and flow cytometry further confirmed that fluorescent labeled PGNPs (f-PGNPs) maintained a high cellular PTX level in both H460 and H460PTX cells. These results demonstrated that nano-drug conjugates were able to avoid the development of drug resistance in sensitive cells and evade Pgp-mediated drug resistance and to maintain a high cytotoxicity in drug-resistant cancer cells. These findings exemplify a powerful nanotechnological approach to the long-lasting issue of chemotherapy-induced drug resistance.